»Synd, Forbrydelser og Laster«. Forbryderen i 1800-tallets Danmark - Holst Scherg, Rune (Historisk Tidsskrift, 2013)
Sin, Crimes and Vices The criminal in 19th Century Denmark This article deals with the criminological thinking in Denmark in the period between 1789 - when a highly influential legislation on larceny was passed - and 1866 when a grand Penal Reform was introduced. The article is predominantly based on published material in the form of religious, legal, philosophical, psychological and quasi-academic literature dealing with the nature of Man and the reason of crime. During the European Enlightenment, traditional Christian doctrines about Man as having no Free Will and being sinful in nature were challenged by modern ideas about Man as free, rational, and inherently good. Generally, three perspectives on the criminal emerged from the Enlightenment: 1) a liberal/ liberal-conservative perspective highlighting the criminal as a free and rational (and therefore) immoral individual; 2) a contextual perspective emphasising the criminal as shaped by the environment; and 3) a structural perspective, representing the criminal as a (natural) by-product of structural conditions. In Denmark the liberal-conservative view of Man and the criminal (primarily associated with the German philosopher Immanuel Kant) dominated from the 1790s and onwards, although more contextual ideas gradually became incorporated in this bourgeois understanding of crime. At the root of crime was ’lust’ in all its manifestations e.g. gambling, drunkenness, and sexual desire. Fundamentally, the criminal was a person who acted on his immoral impulses emanating from either evil will or an undeveloped moral sense. This understanding of the criminal comprised the foundation of the Larceny Legislation of 1789. In the following decades, this conventional bourgeois understanding of Man was frequently challenged by more materialistic and deterministic perspectives. Particularly, Gall’s Phrenology became popular, but never gained permanent influence on the dominant discourse on Man and the criminal. Likewise, in 1824, the Danish doctor F.G. Howitz challenged the dominant discourse by claiming that Man essentially was constituted by his biology and his milieu. Although his ideas did not catch on immediately, many of his ideas can be seen in later psychiatric-medical discourses. In spite of his and even others’ fundamental critique of the Kantian principles underlying the liberal-conservative view of Man, the Penal Reform of 1866 was to a large extent founded on exactly these Kantian principles. Ultimately, the bourgeois understanding of Man and the criminal was challenged by the growing influence of the field of psychiatry and moral statistics. These newly constructed scientific disciplines rather successfully questioned the key assumptions underlying the previous understanding of man as malleable and possessing a free will. By using positivistic methods generated from the natural sciences, which by this time had been elevated in the scientific hierarchy, they managed what other deterministic systems before had not been able to. The above description of the development of criminological discourses may be seen in relation to the overall development of the ’scientification’ of scholarly discourse in the field of humanities and the process of secularisation. Additionally, it seems reasonable to view the construction of the ’immoral criminal’ in relation to the construction of a distinctly bourgeois cultural identity. Similarly, it can be argued that the construction of the bourgeois ideal and the criminal being immoral, but at the same time malleable is associated with a new ordering of the mechanisms of social control and discipline.